2010
DOI: 10.1007/s00213-010-1819-6
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioids and the modulation of pain

Abstract: The pharmacological profile of KOP agonists in visceral pain models suggest that peripherally restricted KOP agonists are potentially useful for a variety of peripheral pain states. Further, clinical investigation of peripherally restricted KOP agonists will help to clarify the painful conditions where KOP agonists will be most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 116 publications
(137 reference statements)
3
113
0
5
Order By: Relevance
“…Still another study reported that peripherally administered -opioid receptor agonists were antinociceptive, but that the effect was not blocked by -opioid receptor antagonists (35). The resolution to these different findings may lie in the modality, location, and intensity of the noxious stimulus applied to the periphery (16,21,25). Our finding that spinal -opioid receptor stimulation attenuated the exercise pressor reflex in rats with ligated femoral arteries raises the issue of whether the -opioid receptors stimulated by U62066 were located on the central endings of group III and IV afferents or were located postsynaptically on interneurons in the dorsal horn of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Still another study reported that peripherally administered -opioid receptor agonists were antinociceptive, but that the effect was not blocked by -opioid receptor antagonists (35). The resolution to these different findings may lie in the modality, location, and intensity of the noxious stimulus applied to the periphery (16,21,25). Our finding that spinal -opioid receptor stimulation attenuated the exercise pressor reflex in rats with ligated femoral arteries raises the issue of whether the -opioid receptors stimulated by U62066 were located on the central endings of group III and IV afferents or were located postsynaptically on interneurons in the dorsal horn of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Êðîìå òîãî, â íàñòîÿùåå âðåìÿ ïðîâîäèòñÿ ñåðèÿ äîêëèíè÷åñêèõ èññëåäîâàíèé TRK-820 â êà÷åñò-âå ñåëåêòèâíîãî ê k-ðåöåïòîðàì àíàëüãåòèêà, ñðåäñòâà äëÿ ëå÷åíèÿ íåéðîïàòè÷åñêîé áîëè, ëåêàðñòâåííîé çà-âèñèìîñòè, øèçîôðåíèè, äèñêèíåçèè [109 -111].  íàñòîÿùåå âðåìÿ àêòèâíî ðàçâèâàåòñÿ íàïðàâëå-íèå ñîçäàíèÿ ïåðèôåðè÷åñêè-ñåëåêòèâíûõ êàïïà-ëè-ãàíäîâ [1,3,25,30]. Ïåðâûì òàêèì ïåðèôåðè÷åñêè-ñå-ëåêòèâíûì êàïïà-àãîíèñòîì ÿâèëñÿ ôåäîòîöèí (ðèñ.…”
Section: -(1-áåíçîôóðàí-4-èë)-n-ìåòèë-n-[(5r7s8s)-7-ïèððîëèäèí-1-èmentioning
confidence: 99%
“…Ýòîò ïåðèôåðè÷å-ñêèé àãîíèñò k-ðåöåïòîðîâ ïîêàçàë âûñîêóþ ýôôåê-òèâíîñòü ó ïàöèåíòîâ ñ õðîíè÷åñêèì ïàíêðåàòèòîì [116] è â íàñòîÿùåå âðåìÿ ïðîõîäèò II ôàçó êëèíè÷å-ñêèõ èñïûòàíèé ïðåïàðàòîâ äëÿ òåðàïèè ïîñëåîïåðà-öèîííîé è âèñöåðàëüíîé áîëè [1,25]. Ñòðóêòóðíî ñõî-aeåå ñîåäèíåíèå ADL 10 -0116 íàõîäèòñÿ íà I ôàçå êëèíè÷åñêèõ èñïûòàíèé äëÿ ëå÷åíèÿ õðîíè÷åñêîé âîñïàëèòåëüíîé áîëè ïðè ðåâìàòîèäíîì àðòðèòå, âèñ-öåðàëüíîé áîëè, à òàêaeå ïðè ñèíäðîìå ðàçäðàaeåííîãî êèøå÷íèêà [111].…”
Section: -(1-áåíçîôóðàí-4-èë)-n-ìåòèë-n-[(5r7s8s)-7-ïèððîëèäèí-1-èunclassified
See 1 more Smart Citation
“…KORs are also expressed by pain-sensing neurons (nociceptors) of the peripheral nervous system, where they function to inhibit transmission of pain stimuli to the CNS (Fields et al, 1980;Chen et al, 1997;Stein and Lang, 2009;Stein and Zollner, 2009;Berg et al, 2011;Jamshidi et al, 2015). It has been suggested that peripherally-restricted KOR agonists may provide for improved treatment of some forms of pain that would be devoid of CNS-mediated adverse effects (Kivell and Prisinzano, 2010;Vanderah, 2010;Berg et al, 2011;Vadivelu et al, 2011;Jamshidi et al, 2015), and some clinical studies have demonstrated efficacy of peripherally-restricted KOR agonists in a variety of pain conditions (Riviere, 2004;Arendt-Nielsen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%